Global Antimicrobial Stewardship: A Closer Look at the Formidable Implementation Challenges - Tiong, John J. L.; Loo, Jason S. E.; Mai, Chun-Wai (Frontiers in Microbiology, 2016)
Antimicrobial stewardship (AMS) has been touted as one of the key strategies required in tackling worldwide escalation of antibiotic resistance. Although AMS has optimized antibiotic usage and reduced the incidence of resistance development in some regions, its full global potential has been curtailed by various AMS-impeding factors. This article seeks to highlight in a detailed perspective, the key challenges that hamper global AMS endeavors, some of which include the paucity of effective implementation strategies that cater for the challenging settings of developing nations, the slow response of governments, uncoordinated AMS activities as well as implementation fragmentation across different sectors and countries. The authors of this article call upon all stakeholders to pay attention to these seemingly obvious but often under-addressed problems. If left unresolved, this may render all current and future AMS initiatives pointless.